Specific Gene- and MicroRNA-Expression Pattern Contributes to the Epithelial to Mesenchymal Transition in a Rat Model of Experimental Colitis - Éva Boros; Marianna Csatári; Csaba Varga; Balázs Bálint; István Nagy (Hindawi Limited, 2017)
The aim of this study was to determine the gene- and microRNA-expression profile contributing to epithelial to mesenchymal transition in a rat model of experimental colitis. For this, inflammation was induced by injecting 2,4,6-trinitrobenzene sulphonic acid to the colon of male Wistar rats. Samples were taken from both inflamed and uninflamed regions of the same colon, total RNA was isolated, and the mRNA and microRNA expressions were monitored. We have determined that the expression of genes responsible for inducing mesenchymal phenotype, such as Egr1, Fgf2, Fgf7, Jak2, Notch2, Hif1α, Zeb2, Mmp9, Lox, and Vim, was all significantly induced in the inflamed regions of the affected colons while the epithelial marker E-cadherin (Cdh1) was downregulated. In contrast, the expression of microRNAs miR-192, miR-143, miR-375, miR-30a, miR-107, and miR-200b responsible for the regulation of the above mentioned genes was significantly downregulated in inflamed colon. Importantly, we detected moderate induction in the expression of five out of six tested microRNAs in the uninflamed regions. In summary, we identified numerous interacting genes and microRNAs with mutually exclusive expression pattern in inflamed regions of colitis-induced rats. These findings suggest that-among others-an important step in the epithelial to mesenchymal transition in experimental colitis is the dysregulated microRNA expression.